Tool for Monitoring Hillslope Stability Considering Precipitation Data - Peña Rincón, Carlos Arturo (TECCIENCIA, 2019)
We present a methodology applied to the monitoring of the slope stability in the rural area in Manizales, by means of the Boussinesq storage slope (HSB) partial differential equation and theoretical information of hydrogeological parameters, such as porosity, hydraulic conductivity, thickness and other data obtained by indirect measurements with geographic information systems such as the angle of the slope, the width of the slope, the profile of the slope and the precipitation information of the nearest weather station. In this work, the HSB equation is solved with the finite differences method implemented in Python, for four days of the EMAS meteorological station report. The result obtained was of the saturation curve and of the safety factor for each day. This methodology can contribute to the monitoring of hillsides located in rural areas as long as the values of the hydrogeological parameters are adjusted and a way of support of the efforts to implement an early warning system against hazard landslides.